THE EFFECTIVENESS OF THE VILLAGE CONSULTATIVE BODY IN THE IMPLEMENTATION OF GOVERNMENT IN THE VILLAGE - Ade Fahrudin; Ardiana Trisnawiana (SEAN Institute, 2023)
The village consultative body, abbreviated as BPD, is essentially the embodiment of all community members and is a village high institution capable of attending to the community's interests in an area, particularly a village. In practice, however, the BPD is less effective due to the absence of knowledge possessed by its members, and the village government is often nominated by the village chief. Therefore, the purpose of this study is to evaluate the efficacy of the Village Consultative Body (BPD) in implementing village-level governance. This study employs a descriptive research model with data processing techniques and qualitative analysis at BPD Tegalmanggung Village, Cimanggung District, Sumedang Province. The findings of this study indicate that the Village Consultative Body's (BPD) effectiveness in implementing governance in Tegalmanggung Village still confronts several obstacles. Several factors contributed to the ineffectiveness of the BPD, including the fact that members of the BPD held outside jobs, a lack of knowledge about village governance and BPD legislation, and the channeling of individual aspirations.